The Effect of Brain Gym on Psychomotor Development in Preschool Children - Safrudin, Enjela Lala; Ayuningrum , Lia Dian; Wijayanti, Indah (Jurusan PG-PAUD Universitas Halu Oleo,, 2024)
The development of children who are stimulated by their parents regularly and purposefully will develop faster than children who are not stimulated. Most parents do not really understand this, many parents think that if the child is not sick then the child does not experience health problems including growth and development. Stimulation using Brain Gym very important because this method can significantly improve children's brain performance and learning abilities. The purpose of this study was to determine whether there is an effect of Brain Gym the psychomotor development of children aged 3rd-6th years at Harapan Bangsa Playground Pandak and Masyithoh Kauman Kindergarten Bantul. The research technique used was a quasi-experiment with a total sample of 106 children divided into control and intervention groups. Data was collected using the Instrument of Developmental Achievement of Children aged-6th years. The data analysis used is the Mann Withney Test and after being given Brain Gym stimulation, the results of P value 0.000 are smaller than 0.05 (p-value <0.05), these results indicate that Brain Gym has a significant influence on psychomotor development in preschool children